Welding Principles and Applications ( Sách photocoppy ) - Jeffus Larry F. (Thomson Delmar Learning, 2007)
This newly updated sixth edition of Welding: Principles and Applications features tight shots of actual welds to speed beginners to an understanding of a variety of different welding processes used today. Moving quickly from basic concepts to the study of today's most complex welding technologies, each section begins by introducing readers to the materials, equipment, setup procedures, and critical safety information they need to know to successfully execute a specific process. Remaining chapters in the section zero in on individual welding tasks and must-know techniques. Comprehensive coverage spans from specific welding processes to discussion of related topics, including welding metallurgy, metal fabrication, weld testing and inspection, joint design, and job costing. Objectives, key terms, review questions, lab experiments, and practice exercises in every chapter are also included to focus attention on information and skills required for success as a professional welder.